The Influence of Using Smart Multiplication Table Learning Media (Takalintar) on the Learning Outcomes of Grade III Elementary School Students - Teme, Imelda Silvia; Mbuik, Heryon Bernard; Naitili, Cornelia Amanda (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Abstract. Teaching learning activities usually occur between teachers and students. Teachers as learning managers, play a role in creating a comfortable and conducive learning climate. Therefore, as a teacher, you must be able to choose and apply effective learning media to achieve learning goals and be able to attract student learning results. The purpose of this study is to determine the influence of the use of TAKALINTAR learning media on the learning outcomes of students in grade IIIA SD Inpres Kuanino 3. This type of research is quantitative research classified as Quasi Experimental research, using a pretest-posttest- control group design. The sampling technique uses a saturated sampling technique with a sample of 30 respondents. The instruments in this study used observation, test and documentation data. The data was analyzed by normality tests, homogeneity and hypothesis tests using t-tests. The results of this study showed that the average score of the pretest-posttest- of the experimental class and the pretest-posttest- of the control class using the t-test, the posttest of the experimental class and the control class was 84.67 > 75.00 with a difference of 1.98 and the pretest of the experimental class and the control class was 50.67 > 51.33. Further through hypothesis testing (Paired Sample T-test) shows that the value of sig. (2-tailed) t-test for Equality of Means of 0.000 < 0.05 means that H0 is rejected and Ha is accepted. The conclusion of this study is that there is a significant influence of the use of smart multiplication table (TAKALINTAR) media learning on the learning outcomes of grade IIIA students of SD Inpres Kuanino 3.